Simple parking strategies. (19th September 2019) - Krapivsky, P L; Redner, S
Abstract: We investigate simple strategies that embody the decisions that one faces when trying to park near a popular destination. Should one park far from the target (destination), where finding a spot is easy, but then be faced with a long walk, or should one attempt to look for a desirable spot close to the target, where spots may be hard to find? We study an idealized parking process on a one-dimensional geometry where the desired target is located at x = 0, cars enter the system from the right at a rate and each car leaves at a unit rate. We analyze three parking strategies—meek, prudent, and optimistic—and determine which is optimal.